PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING PADA PEMBELAJARAN MATEMATIKA MATERI LINGKARAN KELAS VIII SMP NEGERI 3 TONDANO - Putri Meirona Br. Karosekali; Jorry F. Monoarfa (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2023)
The purpose of this study was to determine the average mathematics learning outcomes of students of SMP Negeri 3 Tondano the circle material with the application of Discovery Learning. The research design was using post-test Control Group Design. The samples taken were students of grade VIII B as an experimental class and class VIII C as a control class at SMP Negeri 3 Tondano with a total of 28 and 26 students respectively. The results of the study in the post-test obtained an average experimental class of 79, 44 and the control class of 74.32. Based on the results of the statistical test of student learning results (t-test) obtained acalculated t value = 3.165 > ttable = 2.016. it can be concluded that student learning outcomes in circle material mathematics subjects taught using the discovery learning model are increased and better than the direct learning model